Examining diversity in public willingness to participate in offshore human biobanking: An Australian mixed methods study. (October 2020) - Critchley, Christine; Wiersma, Miriam; Lipworth, Wendy; Light, Edwina; Dive, Lisa; Kerridge, Ian
To ensure their sustainability and scientific utility, human biobanks are networking internationally. Sharing biospecimens and associated data across jurisdictions raise a number of practical, ethical, legal and social challenges that could reduce the publics' willingness to donate their much needed tissue for research purposes. This research aims to identify the impact of biobank location on willingness to donate through a national quantitative survey ( n  = 750) and 16 in-depth interviews. A latent class analysis in combination with qualitative results suggests that a large proportion of Australians are willing to donate and/or allow their tissue to be stored offshore to help others, but others are reluctant due to uncertainty around foreign ethical and regulatory standards and the loss of potential local benefits. The results highlight for the first time the diversity of public views, and provide important guidance for policy makers and science communicators eager to tailor strategies for specific publics.